2006
DOI: 10.1007/s11258-006-9136-1
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Zones Between Two European Oaks: a Plant Community Approach

Abstract: Phenomena of hybridization can affect the ecology and evolution of the species involved in the process, as well as their communities. Although numerous papers focus upon the problem of taxonomy, few of these have attempted to study hybrid zones in relation to the analysis of their communities. On the Iberian Peninsula, hybridization phenomena among different oak species are frequent. It is, however, between Quercus faginea Lam. and Quercus pubescens Willd. where the most noteworthy hybridization phenomenon occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…The species does not occur above 1500 m because freezing temperatures hinder the establishment and growth of seedlings. As in our study, Sánchez de Dios et al (2006) found that Q. faginea forests on the Iberian Peninsula were associated with continental areas that have low precipitation. The phenology of Q. faginea is similar to that of species that produce roots that can access deep water reserves (Castro and Montserrat 1998).…”
Section: Effects Of Abiotic Factorssupporting
confidence: 81%
“…The species does not occur above 1500 m because freezing temperatures hinder the establishment and growth of seedlings. As in our study, Sánchez de Dios et al (2006) found that Q. faginea forests on the Iberian Peninsula were associated with continental areas that have low precipitation. The phenology of Q. faginea is similar to that of species that produce roots that can access deep water reserves (Castro and Montserrat 1998).…”
Section: Effects Of Abiotic Factorssupporting
confidence: 81%
“…This method has several advantages over other models used for similar interpolations (Sánchez Palomares et al 1999) and has been used in similar studies (Benito Garzón et al , 2007Garzón et al , 2008Sánchez de Dios et al 2006). …”
Section: Climate Variablesmentioning
confidence: 99%
“…The Iberian Peninsula is one of the European regions where transition territories are of greatest importance, both because of their extent and the importance of the plant communities to which they are home (Costa Tenorio et al 1997;Sánchez de Dios et al 2006). Owing to their transitional nature, submediterranean territories are very sensitive to change (Gosz 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In this way we might omit a true hybrid zone (i.e. an area where hybrids would outperform both parental species), which can be located in an ecotone between preferable habitats of parental species (Sánchez de Dios et al 2006). Future studies need to address this aspect as well.…”
Section: Discussionmentioning
confidence: 99%
“…Related oak species can hybridise relatively easily, and hybrids are usually fertile (Whittemore and Schaal 1991;Rushton 1993;Tovar-Sánchez and Oyama 2004;Curtu et al 2007;Peñaloza-Ramírez et al 2010). Furthermore, related oak species can differ in ecological optima (Whittemore and Schaal 1991;Timbal and Aussenac 1996;Petit et al 2004;Sánchez de Dios et al 2006;Gugerli et al 2007), so that they often occupy different niches and can reveal variable adaptation to local environments, making room for exogenous selection (Barton and Hewitt 1985).…”
Section: Introductionmentioning
confidence: 99%